First Report of Pyrenophora tritici-repentis in Wheat (Triticum aestivum L.) in Korea and in vitro Selection of an Effective Fungicide - Min-Hye Jeong; Eu Ddeum Choi; Seol-Hwa Jang; Sang-Min Kim; Sook-Young Park (한국균학회지, 2023)
Tan spot, caused by Pyrenophora tritici-repentis, is a major foliar disease in wheat worldwide. In April 2021, tan spot symptoms were observed in a commercial wheat field in Suncheon, Jeonnam Province, Korea, with over 5% of the wheat leaves exhibiting symptoms. These symptoms included oval-shaped tan necrosis surrounded by a bright halo. The three representative isolates exhibited irregular mycelial growth on V8-potato dextrose agar and produced pseudothecia. Based on the concatenated sequence datasets of four multi-genes, including the internal transcribed spacer, large subunit ribosomal RNA, glyceraldehyde3-phosphate dehydrogenase, and RNA polymerase II second-largest subunit genes, phylogenetic analysis revealed that these three isolates clustered in the same clade as P. tritici-repentis. Results of pathogenicity test indicated that the initial symptoms appeared 5 days post-inoculation (dpi), with typical tan spot symptoms developing at 7 dpi. The pathogen was successfully re-isolated from the symptomatic tissues, thus fulfilling Koch's postulates. Furthermore, we selected three fungicides that effectively inhibited the mycelial growth of P. tritici-repentis by more than 90% in vitro. To the best of our knowledge, this is the first report of tan spot disease in wheat in Korea.